2015
DOI: 10.4103/1319-3767.166205
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin levels in children with chronic liver disease

Abstract: Background/Aim:We aimed to analyze serum hepcidin level in children with chronic liver disease (CLD) and its relationship with serum cytokines level, liver function tests, hepatic iron content, and liver fibrosis.Patients and Methods:The study included 34 children with CLD, and 15 age- and gender-matched healthy children. Serum hepcidin, ferritin, iron level, interleukin-6 (IL-6), transforming growth factor-β (TGF-β ), total oxidant status (TOS), and antioxidant status (TAS) were studied in all patients and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…33 Hence, in patients with hepatic dysfunction such as liver cirrhosis, decreased levels of hepcidin might result in the upregulation of ferroportin and accelerated efflux of iron from iron storage areas, eg, the GP. 34 A prior case report described a rare hereditary metabolic disease with liver cirrhosis, dystonia, and hypermanganesemia. 29 There was some similarity between that reported case and the patients in the T 1 h group in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Hence, in patients with hepatic dysfunction such as liver cirrhosis, decreased levels of hepcidin might result in the upregulation of ferroportin and accelerated efflux of iron from iron storage areas, eg, the GP. 34 A prior case report described a rare hereditary metabolic disease with liver cirrhosis, dystonia, and hypermanganesemia. 29 There was some similarity between that reported case and the patients in the T 1 h group in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This key peptide of iron metabolism is mainly produced by the liver . Hence, in patients with hepatic dysfunction such as liver cirrhosis, decreased levels of hepcidin might result in the upregulation of ferroportin and accelerated efflux of iron from iron storage areas, eg, the GP . A prior case report described a rare hereditary metabolic disease with liver cirrhosis, dystonia, and hypermanganesemia .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the hepcidin:ferritin ratio was lower in CLD patients and further decreased as fibrosis progressed[112]. Similarly, another study showed that in children with CLD, as the severity of fibrosis increased, hepcidin:ferritin ratio decreased, while serum ferritin and transferrin saturation remained high[113]. These studies present hepcidin as a valuable marker of fibrosis progression.…”
Section: Iron-assisted Assessment Of Liver Fibrosismentioning
confidence: 99%
“…When hepcidin values are corrected by iron-load (by using hepcidin/ferritin ratio), they show low values in patients with severe liver fibrosis (Cakir et al 2015 ). What is more important this ratio can differentiate between advanced fibrosis and lack of fibrosis (Tan et al 2012 ).…”
Section: Low Hepcidin As a Biochemical Marker In Liver Fibrosismentioning
confidence: 99%